Impacts Minimum Number Of Combination On Farm Man-Days And Fertilizer Dosage Application To Rice (Oryza Sativa.L) Grain Yield In Sub District Majalaya, Karawang Regency On Covid-19 Pandemic Period - Wagiono; Zohrah, Laila; Fitriani, Risma (Jurnal Agrotek Indonesia, 2021)
This study aims to know minimum number of a combination on farm man-days and fertilizer dosage used to rice (Oryza Sativa.L) grain yield on Large Scale Social Distancing (LSCD) period implemented caused by Covid-19 pandemic in Karawang Regency the research was conducted in Majalaya village, Karawang Regency from August to December 2020. An experimental method had been carried out based on a randomized block design which consisted of three number on farm man-days used combined by three dosage of fertilizer treatments, i.e., T1 (number man-days 100%+ dosage fertilizers 100%), T2 (number man-days 100% + dosage fertilizers 80%), T3 (number man-days 100%+ dosage fertilizers 60%), T4 (number man-days 80%+ dosage fertilizers 100%), T5 (number man-days 80%+ dosage fertilizers 80%), T6 (number man-days 80%+ dosage fertilizers 60%), T7 (number man-days 60%+ dosage fertilizers 100%), T8 (number man-days 60%+ dosage fertilizers 80%), T9 (number man-days 60%+ dosage fertilizers 60%). There were 3 times replication. Observed variable was rice grain yield (tons/hectare). Results indicated that the aplication at T1 to T9 significantly different to almost all obeserved variable and application at T1 (5.85 tons/hectare) was the best, but it was not significant to T4 (5.80tons/hectare). Suggestion for rice farmers in around of Karawang Regency, that rice farming feasibles on New Normal Adaptation Period by minimum number on farm man-days used must be more than 80% recommended man-days used and 80% of fertilizer dosage fertilize standard application.